Modeling distributed embedded control system and application code generation using IEC 61499 function blocks and XML - Sreenidhi Koti Ananda Rao. (2008)
In this project the IEC-61499 Function Block (draft) standard for process control is explored and it will be investigated how IEC-61499 can be used for typical design problems when designing control applications in Distributed Real-time Embedded (DRE) systems. IEC-61499 will become the atomic unit of control for the DRE systems.